Wokół nowej edycji Cichych bohaterek Marii Bruchnalskiej. Tom I Ciche bohaterki 1863. Udział kobiet w powstaniu styczniowym, ss. 543, tom II Ciche bohaterki 1863. Kobiety Litwy – Wołynia – Ukrainy, ss. 333, opracowanie naukowe, komentarz i przypisy Lidia Michalska – Bracha i Emil Noiński, wydawnictwo Muzeum Historii Polski, Zakład Narodowy im. Ossolińskich, Warszawa – Wrocław 2024. - Kostrzewska, Ewelina Maria (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
Artykuł jest krytyczną recenzją dwutomowej monografii: Ciche bohaterki 1863. Udział kobiet w powstaniu styczniowym (t. 1); Ciche bohaterki 1863. Kobiety Litwy – Wołynia – Ukrainy (t. 2) - opracowanie naukowe, komentarz i przypisy Lidia Michalska – Bracha i Emil Noiński, wydanej w 2024 r. przez Zakład Narodowy im. Ossolińskich we Wrocławiu.

The article is a critical review of the two-volume monograph: Silent Heroines 1863. The Participation of Women in the January Uprising (Vol. 1); Silent Heroines 1863. Women of Lithuania – Volhynia – Ukraine (Vol. 2), edited, annotated, and commented on by Lidia Michalska-Bracha and Emil Noiński, published in 2024 by the Ossoliński National Institute in Wrocław.
On the New Edition of Maria Bruchnalska’s Silent Heroines. Volume I: Silent Heroines 1863. Women’s Participation in the January Uprising, 543 pp.; Volume II: Silent Heroines 1863. Women of Lithuania – Volhynia – Ukraine, 333 pp.; scientific edition, commentary, and notes by Lidia Michalska-Bracha and Emil Noiński; published by the Museum of Polish History, Ossoliński National Institute, Warsaw – Wrocław, 2024 ​
Keywords: Powstanie styczniowe; historia kobiet; Litwa; Wołyń; Ukraina; January Uprising; women’s history; Lithuania; Volhynia; Ukraine